(untitled) (Nigerian Journal of Technology, 2017)
This study investigates the physical and mechanical properties of two timber species for structural use. Three logs of each specie were obtained at different areas of Kwara State, of Nigeria which is located north in the periphery of the south-western rain forest area, sliced into 2” by 12” size before seasoning naturally and their structural/strength properties were determined at a moisture content of 18%. These logs were cut into test samples for the determination of their properties. A total of 351 samples (45 samples for each test) free from visible defects was used for each specie. Basic physical properties of the samples like moisture content, specific gravity and density was determined. Tensile strength, modulus of rupture, modulus of elasticity, compression, shear and hardness were the mechanical tests carried out according to BS 373 (1957), CP112 (1971), NCP2 (1973), EC5 (1995) and BS 5268 (2002) specifications on Universal Testing Machine (UTM). Results were analysed statistically using Analysis of Variance (ANOVA). A. Indica was graded into strength class D40 while X. Aethiopica was grade into strength class D70. http://dx.doi.org/10.4314/njt.v36i4.2